Bakhtiniana 15 anos: interação de ciência, arte e vida - Brait, Beth; Cruz Pistori, Maria Helena; Lopes-Dugnani, Bruna; Stella, Paulo Rogério; Gontijo Rosa, Carlos; Jovelina Storto, Letícia; Godinho de Alcântara, Regina (Bakhtiniana. Revista de Estudos do Discurso, 2024)
Editorial